Effects of artifact removal on cone-beam computed tomography images - Hooriyeh Bashizade Fakhar; Raheleh Emami; Kave Moloudi; Farzaneh Mosavat (Wolters Kluwer Medknow Publications, 2018)
Background: Dental implants and metal fillings may cause artifacts in cone-beam computed tomography (CBCT) images and reduce image quality and anatomic accuracy. The purposes of this study are a subjective evaluation of anatomic landmarks and linear bone measurements after applying artifact removal (low-medium) option on CBCT images. Materials and Methods: In this cross-sectional study, thirty CBCT images from thirty qualified patients were selected in a private radiology center. Low and medium artifact removal was applied to images. Three radiologists assessed the visibility of the mandibular canal, mental foramen, and lamina dura in images. Crestal width and bone length were also measured in three groups of images and was compared by exact McNemar test. ICC test (two-way random model, absolute agreement types) was calculated for comparison of linear bone measurements in three images groups. P ≤ 0.05 was considered statistically significant. Results: Percent agreement of determining mental foramen (outline and location), mandibular canal (outline and location), and lamina dura between three groups of images were 100%, 100%, 83.3%, 96.7%, and 56.6%, respectively. The results of exact McNemar test revealed that medium artifact removal group had a statistical difference in lamina dura observation with none and low artifact removal groups (P < 0.001). Intraclass correlation coefficient showed no statistical differences in crestal width and bone length between groups (P < 0.001). Conclusion: Applying artifact removal does not affect the visibility of large anatomical structures and linear bone measurements, but delicate structures such as lamina dura may become less clear after artifact removal.